Plausible Pnicogen Bonding of epi-Cinchonidine as a Chiral Scaffold in Catalysis - Ullah, Zakir; Kim, Kang; Venkanna, Arramshetti; Kim, Hye su; Kim, Moon Il; Kim, Mi-hyun (Frontiers in Chemistry, 2021)
As a non-covalent interaction of a chiral scaffold in catalysis, pnicogen bonding of epi-cinchonidine (epi-CD), a cinchona alkaloid, was simulated to consider whether the interaction can have the potential controlling enantiotopic face like hydrogen bonding. Among five reactive functional groups in epi-CD, two stable complexes of the hydroxyl group (X-epi-CD1) at C17 and of the quinoline ring (X-epi-CD2) at N16 with pnictide family analytes [X = substituted phosphine (PX), i.e., F, Br, Cl, CF3, CN, HO, NO2, and CH3, and pnictide family analytes, i.e., PBr3, BiI3, SbI3, and AsI3] were predicted with intermolecular interaction energies, charge transfer (QMulliken and QNBO), and band gap energies of HOMO–LUMO (Eg) at the B3LYP/6-31G(d,p) level of density functional theory. It was found that the dominant site of pnicogen bonding in epi-CD is the quinoline ring (N16 atom) rather than the hydroxyl group (O36 atom). In addition, the UV-Vis spectra of the complex were calculated by time-dependent density functional theory (TD-DFT) at the B3LYP/6-31+G(d,p) level and compared with experimental measurements. Through these calculations, two intermolecular interactions (H-bond vs. pnicogen bond) of epi-CD were compared.